2021
DOI: 10.1109/tps.2020.3026781
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of QED Effects With Varying Z in Thin Foil Targets

Abstract: Quantum electrodynamics (QED) effects in intense laser plasma interaction were investigated using Particle in Cell (PIC) simulations, specifically the generation of electron-positron pairs. Linearly polarized intense laser pulses were used to irradiate a thin foil (1 μm) with an intensity of 4×10 23 Wcm -2 . A scan of targets with varying Z (Al, Cu and Au) is investigated to determine the effect of target Z/density on electron-positron pair production. The total number of pairs created for Al and Cu targets is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As shown in figure 3(c), the sheath field is notably stronger for the structured target. Figure 4 presents the density distribution of electrons and photons, revealing two orders of significant enhancement in photon density compared to our previous work [32]. In a recent simulation study by Zi et al suggests that the pair production can be enhanced using an aluminum (Al) target with varying transverse target sizes, employing two laser beams.…”
Section: Simulation Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As shown in figure 3(c), the sheath field is notably stronger for the structured target. Figure 4 presents the density distribution of electrons and photons, revealing two orders of significant enhancement in photon density compared to our previous work [32]. In a recent simulation study by Zi et al suggests that the pair production can be enhanced using an aluminum (Al) target with varying transverse target sizes, employing two laser beams.…”
Section: Simulation Results and Discussionmentioning
confidence: 76%
“…We have compared the results of the structured target with a solid flat target, and found that the Breit-Wheeler (BW) process dominates over the positron generation process. Using the two-dimensional (2D) PIC code EPOCH [31], we were able to demonstrate by modelling over 10 9 positrons with a cutoff energy 2.5 GeV, which was twice the energy achieved in our previous work with the same laser intensity [32]. We have proposed a new theoretical model for magnetic field associated with the phenomenon and shown relevancy between theoretical and simulation results of some important parameters.…”
Section: Introductionmentioning
confidence: 73%
“…In ultra-intense laser-plasma interactions(I > 10 22 W/cm 2 ), quantum electrodynamics (QED) effects play a dominant role [11,12], leading to the emission of high-energy gamma rays and pair production. Nonlinear Compton scattering and the resulting radiation reaction and pair production by the Breit-Wheeler processes [13] have been incorporated into particle-in-cell (PIC) codes like EPOCH [14] to study the QED processes in laser-plasma interactions [15][16][17][18]. When an ultra-intense laser interacts with a foil, the two main processes leading to emission of gamma rays are bremsstrahlung and nonlinear Compton scattering (NCS).…”
Section: Introductionmentioning
confidence: 99%